Validation of a biochip array technology for multi-mycotoxins screening in Rice and other cereals - Filipa Carreiró; Sílvia Cruz Barros; Carla Brites; Andreia Freitas; Fernando Ramos; Ana Sanches Silva (Food Chemistry Advances, 2024)
Cereal grains are widely cultivated agricultural commodities, and they constitute a key source of energy. However, many of them are affected by fungal contamination, and consequently, by the presence of mycotoxin. The development of monitoring techniques to evaluate exposure, is therefore of interest. Immunoassays have recently emerged as potential alternatives for the study of mycotoxins. This study focuses on a validation of a biochip array technology (BAT) for multi-mycotoxins screening in oat, barley, rye, and wheat grains. The Evidence Investigator Myco 7 (RANDOX Food Diagnostic), based in a competitive chemiluminescent immunoassay, was used for the simultaneous semi-quantitative detection of the mycotoxin's immunoassays. According to validation results, spiked rice samples showed low false results (5 % of false negatives and 5 % of false positives for fumonisins, 5 % of false negatives for Zearalenone, Aflatoxin B1, T2HT2 and Deoxynivalenol and 5 % of false positives were found for ochratoxin A). In the spiked samples of other cereals, were found 5 % of false positives for fumonisin B1+fumonisin B2, zearalenone, ochratoxin A and aflatoxin B1 and 5 % of false negatives were found for Fumonisin 1 + Fumonisin 2, Ochratoxin A, Aflatoxin B1 and T2+HT2 in agreement with European Union legislation performance criteria. This BAT immunoassay provides important benefits for the rapid and efficient screening of several mycotoxins in cereal grain samples at various levels.